When Digital Vocabulary Learning Meets Student Engagement: Comparing HyperCard and Hypertext Models in EFL Classrooms - Tatu Munawaroh; Meliyawati; Suryadi (Universitas Hamzanwadi, 2026)
Vocabulary mastery is essential for English as a Foreign Language (EFL) learners because it supports reading comprehension, listening accuracy, writing fluency, and oral communication. However, vocabulary instruction is still frequently dominated by memorization and decontextualized exercises, which may limit students’ lexical development and engagement. This study examined the effects of HyperCard and hypertext learning models on students’ vocabulary mastery by considering different levels of student engagement. A quantitative experimental design with a 2×3 factorial arrangement was employed. The participants were 100 eleventh-grade students from a senior high school in Pandeglang, Indonesia, selected from a population of 245 students. Data were collected through vocabulary pre-tests and post-tests and a student engagement questionnaire. The data were analyzed using descriptive statistics, two-way ANOVA, and Tukey’s post-hoc test. The findings showed that the learning model had a significant effect on students’ vocabulary mastery, with the HyperCard model producing higher post-test scores than the hypertext model. Student engagement also significantly affected vocabulary mastery, as highly engaged students achieved better vocabulary outcomes than students with medium and low engagement. In addition, a significant interaction was found between learning models and engagement levels, indicating that the effectiveness of digital vocabulary instruction varied according to students’ engagement. These findings suggest that structured, card-based, and multimodal vocabulary learning can enhance students’ lexical development, particularly when supported by active learner engagement. The study implies that EFL teachers should integrate digital vocabulary models with instructional strategies that promote students’ attention, participation, persistence, and meaningful use of new words.